Estudio de factibilidad para la creación de una empresa productora de cojines a base de materiales reciclables y su comercialización en el cantón Ambato - Jarrín Chávez, José Edgar (2015)
The overall objective of this thesis is " Develop a feasibility project for the creation of a producer and marketer of tablecloths and napkins and marketing company in the city of Amanita ," the work was developed with the use of library materials , office and technology , and research methods as inductive , statistical and mathematical and same techniques were applied as observation and survey , is last was conducted in a sample of 379 families living in the Parish of Nueva Loja and 62 local selling similar products . The main results were: • In the study of market demand for tablecloths and napkins of 39,042 units and an offer of 27,240 was a determined tablecloth, so there is an unmet demand for 11,802 units. • The technical study found that the company will have an installed capacity of 5,295 tablecloths and cloth napkins per year capacity. Being a new product that requires some time to position themselves in the market it is prudent to begin with 80% of installed capacity percentage will be increased by 5% annually to reach 100 % capacity. • The company will be located in the province of Tungurahua, Canton Ambato, Avenue Simon Bolivar y Road Juan Leon Mera. • The organizational study the need to hire people who will occupy 9 6 different positions were determined. The company consists of six hierarchical levels, which facilitate the flow of information • Legally the company will be incorporated as a Limited Liability Company, will be composed of three members, and "Linen Rubin" will be called, his business is the production and marketing of tablecloths and napkins for dining tables, life is 5 years. • In the economic study found that implementation of the project requires an investment of $ 23,161.23 • Sales prices for the first year of production are: oval and rectangular tablecloth for 4 people at $ 24.33, 6 people $ 31.06; 8 people $ 35.62, and the circular tablecloth table of 4 persons $ 19.98. • It is expected that the utility of the first year of life of project is $ 13,354.96 and a cash flow of $ 14,902.07, in the fifth year a profit of $ 20,232.46 and a cash flow of $ 22,612.08 will be reached. • The financial evaluation was carried out through the main indicators , the application showed the following results: a positive NPV of $ 35,790.20; IRR of 65.85% which is higher than the cost of capital rate of 15 %; RC / B $ 1.24 indicating that for every dollar invested company makes a profit of $ 0.24 dollars; capital is recovered within 1 year and 6 months and finally in the sensitivity analysis it was determined that the project supports increased costs of up to 13.90% and a decrease in revenues of up to 11.20% . In all phases of the study was obtained favorable results thus project implementation is recommended, as it will benefit economically and socially to the parish Canton Ambato, as sources of employment will be generated, boosting manufacturing